Legal Politics of Handling Children as Perpetrators of Criminal Acts: A Comparison of Indonesia and the Philippines from the Perspective of Customary Law and Children's Rights - Raodiah, Raodiah; Wardani, Dian Eka Kusuma; Muhiddin, Nurmiati; Tee-Anastacio, Princess Alyssa D. (SASI, 2025)
Introduction: The treatment of children as perpetrators of criminal acts has become a significant issue in the development of modern law, particularly with regard to the protection of children’s rights and the integration of local values. Indonesia and the Philippines, as countries with different legal traditions, present an important dynamic for study.Purposes of the Research: The purpose of this research is to analyze the differences in the legal politics of Indonesia and the Philippines in addressing juvenile offenders, focusing on the implementation of diversion in Indonesia and the juvenile justice system in the Philippines, while also examining the integration of customary or community-based mechanisms and the protection of children’s rights in both jurisdictions.Methods of the Research: This study employs normative legal research with comparative and conceptual approaches. Data were collected through literature review of statutory provisions, academic doctrines, scholarly literature, and relevant international instruments on children’s rights. The analysis was conducted qualitatively and descriptively to compare norms, practices, and the implications of legal politics in both countries.Results of the Research: The findings of this study demonstrate that the legal politics of both countries, through the integration of customary law and the protection of children’s rights, serve as a fundamental basis for the normative framework in addressing children as perpetrators of criminal acts. In Indonesia, customary law is implicitly integrated through the mechanism of diversion as regulated in Laws of the Juvenile Criminal Justice System. In contrast, in the Philippines, customary or community-based law is explicitly integrated by involving the barangay tanod in handling juvenile offenders during the diversion process under the Juvenile Justice and Welfare Act of 2006 (RA 9344). These findings contribute to advancing Indonesia’s legal policy toward a more humane, inclusive, and internationally aligned juvenile justice system.